Hacia la constitución de una economía de mercados jerárquicos: Modernización capitalista y tradicionalismo social en los industriales chilenos (1952-1958) - Joaquín Fernández Abara; Margarita Goldflam Leiva (Les Cahiers ALHIM)
The article discusses the transformations experienced by the Sociedad de Fomento Fabril (SOFOFA), the main industrial business association of Chile, during the second government of Carlos Ibáñez del Campo. The authors argue that the SOFOFA developed an economic policy program that rejected the state intervention in industry and the growth of the state apparatus, while maintained a protectionist attitude and a productivist discourse. This program was accompanied by a traditional and hierarchical understanding of labor relations, and a growing distrust of politicians and to the autonomous technocratic cadres in the state. These elements allowed the industrialists to develop a pragmatic and flexible attitude in the framework of the debate between structuralists and monetarists and to the policies of the Klein-Saks Mission. It also foreshadowed many of the features of later development of the Chilean right wing political forces.